Stakeholder dialogue for improved local water governance [Part 1. Components of drought planning. 1.2. Organizational component] - Laban P.; Barghout M.; Moriarty P.; Sarsour S. (Drought management guidelines technical annex, 2007)
Stakeholder dialogue and concerted action (SDCA) is an active and facilitated approach to bring different actors to strategic consensus on how to work together on specific issues of shared concern. It does this by making explicit the different opinions of the actors involved. It identifies opportunities to improve the exchange of information, social organization, and decision-making between stakeholders in order to create the proper conditions for innovations. Indeed SDCA enhances institutional and technological innovation through active networking, involving all relevant actors including community members, governments, NGOs, academic institutions, and the private sector. SDCA is used here as the approach to social organization for the implementation of a planning cycle for integrated water resource management (IWRM) and improved water governance in Egypt, Jordan and Palestine.